Assessing Institutional Readiness of East-Asian Countries to Pass over to Technologies of Hydrogen Power Engineering - K. A. Korneev (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
Such states of East Asia as China, Japan, the Republic of Korea depend seriously on import of primary power resources. No wonder, they do their best to extend possibilities of renewable power engineering as the industry, which could cut volumes of crude oil, natural gas and coal import and provide higher power independence. The accident at the Fokusima-1 nuclear power station resulted in re-estimation of the place and role of nuclear power stations in the power generation structure not only in Japan. It formed another ground for accelerated introduction of renewable power engineering technologies. Apart from traditional solar and wind power stations we can see brand new solutions, among them the use of hydrogen for power needs. These technologies came into being in the 1960s – 1970s but only in the 2000s and later the acceptable level of security was reached as well as, at least partial commercial efficiency of using hydrogen as a power source in industry, municipal sector and transport. The article provides information about the readiness of formal institutions in the mentioned-above countries to pass over to hydrogen power plants, it also studies the present day investment mechanisms of supporting business in this field. To do this we should analyze the legal base of activity regulation in the sphere of production and consumption of hydrogen for power needs in China, Japan and the Republic of Korea and to compare results attained in this direction. This analysis could estimate a potential niche for Russia as an exporter of power hydrogen. Russia possesses all necessary resources for getting green hydrogen with the help of the hydrolysis method at hydroelectric stations. It is an acute trend as the ecologic situation in East-Asian states is continuously deteriorating.